The relationship between family adjustment and expatriate performance - D. Trompetter; M. Bussin; R. Nienaber (South African Journal of Business Management, 2016)
Following the global economic collapse, executives are significantly more demanding in understanding the Return on Investment of employee-related programmes including expatriate programmes. Expatriates are defined as employees who are recruited to provide a service in a country which is not the country of residence, typically for at least three years. Expatriate programmes carry high risk; even more so when the family accompanies the employee. The cost of an expatriate assignment is, on average, three times higher than that of a local; yet the failure rate is estimated to be up to 40%. Despite the cost, expatriate resources are critical to embed culture, policies and transfer of skills to a host country environment. The objective of this study was to identify the relationship between the adjustments of the expatriate's family in the hostcountry on the performance of expatriates. The study was conducted using a quantitative research approach. A convenience sample was used and 81 expatriates completed the questionnaire. The results confirmed home to work spillover and that expatriates would value more organisational support for families in the new location. The length of stay in the host location was linked to higher levels of performance – the longer the assignment, the better the performance levels of the expatriate. Human Resources Practitioners can develop support programmes to ensure that expatriates and families are equipped to enhance their adjustment period and consequently positively impact the expatriate's performance whilst on assignment.
Keywords: 650